Christian theology and religious pluralism: a critical evaluation of John Hick - Nah, David S. (Pickwick Publ., 2012)
Religious pluralism and John Hick -- Hick's philosophy of religious pluralism -- Hick's theology of religious pluralism -- An evaluation of Hick's historical arguments -- An evaluation of Hick's conceptual arguments